Answer:
Step-by-step explanation:
------(I)
(i) The product of the two expressions is equal to the product of their factors. (ii) The product of the two expressions is equal to the product of their H.C.F. and L.C.M. 2.
I don't think it can becauze of u count the squares and try 2 plan out the triangle u cant or i should say me i cant see a triangle being formed
Answer:
The error she made was that she was adding x and 2.75. She should subtract 2.75 from x.
Another mistake that she made was that she sold each for $7 assuming that she would make a profit of 78, but she should see each necklace for $12.5 so that she could make a profit of $78.
Step-by-step explanation:
The error she made was that she was adding x and 2.75.
She should write the equation as 8 (x - 2.75) = 78; as she spends $2.75 to make a necklace.
By using the correct equation: 8 (x - 2.75) = 78
=> 8x - 22 = 78
=> 8x = 78 + 22
=> 8x = 100
=> x = 100/8
=> x = 12.5
Another mistake that she made was that she sold each for $7 assuming that she would make a profit of 78, but she should see each necklace for $12.5 so that she could make a profit of $78.
Hope this helps you.
Answer:
Step-by-step explanation:
It's like solving any equation, except we have letters instead of numbers .
k = 3tm + rs {subtract rs from both sides}
k - rs = 3tm {divide both sides by (3m)}
{swap sides}
m≠0
{m must be ≠0 because you cannot divide by 0. There is no t for m=0}